Exploring pathways towards improving patient experience of robot‐assisted radical prostatectomy (RARP): assessing patient satisfaction and attitudes. (May 2018) - Reynolds, Bradley R.; Bulsara, Caroline; Zeps, Nik; Codde, Jim; Lawrentschuk, Nathan; Bolton, Damien; Vivian, Justin
Abstract : Objective: To determine patient satisfaction and experience after robot‐assisted radical prostatectomy (RARP) for prostate cancer, using a convergent mixed‐method qualitative analysis approach. Patients and Methods: 412 patients who underwent RARP between January 2014 and June 2016 were mailed questionnaires and invited to participate in focus groups. Qualitative data was thematically analysed using NVivo. Descriptive statistics were obtained from the questionnaire using SPSS. Results: 214 patients responded (52% of sample size) of whom 97.6% were satisfied and 91.1% would likely recommend RARP. Key themes from the qualitative data highlighted the psychosocial impacts of the diagnosis and RARP process. The importance of early recovery, the benefits of pelvic floor exercises and educational resources were emphasised. Conclusion: Patients were overwhelmingly satisfied with RARP, largely due to relevance and timeliness of the information and support provided both before and after surgery. With an increased understanding of the factors and outcomes that are most important to patients regarding all aspects of hospital care, we can create more targeted care pathways. Key themes will help inform the implementation of an enhanced recovery after surgery (ERAS) protocol to further improve recovery and early return to function.